Pyridylidene ligand facilitates gold-catalyzed oxidative C–H arylation of heterocycles - Hata, Kazuhiro; Ito, Hideto; Segawa, Yasutomo; Itami, Kenichiro (Beilstein Journal of Organic Chemistry, 2015)
Triaryl-2-pyridylidene effectively facilitates the gold-catalyzed oxidative C–H arylation of heteroarenes with arylsilanes as a unique electron-donating ligand on gold. The employment of the 2-pyridylidene ligand, which is one of the strongest electron-donating N-heterocyclic carbenes, resulted in the rate acceleration of the C–H arylation reaction of heterocycles over conventional ligands such as triphenylphosphine and a classical N-heterocyclic carbene. In situ observation and isolation of the 2-pyridylidene-gold(III) species, as well as a DFT study, indicated unusual stability of gold(III) species stabilized by strong electron donation from the 2-pyridylidene ligand. Thus, the gold(I)-to-gold(III) oxidation process is thought to be facilitated by the highly electron-donating 2-pyridylidene ligand.
Keywords: carbene ligand; C–H arylation; gold catalysis

(untitled) - Arcadi, A. (Chem. Rev., 2008)

(untitled) - Hashmi, A. S. K.; Rudolph, M. (Chem. Soc. Rev., 2008)

(untitled) - Li, Z.; Brouwer, C.; He, C. (Chem. Rev., 2008)

(untitled) - Marion, N.; Nolan, S. P. (Chem. Soc. Rev., 2008)

(untitled) - Patil, N. T.; Yamamoto, Y. (Chem. Rev., 2008)

(untitled) - Corma, A.; Leyva-Pérez, A.; Sabater, M. J. (Chem. Rev., 2011)

(untitled) - Huang, H.; Zhou, Y.; Liu, H. (Beilstein J. Org. Chem., 2011)

(untitled) - Rudolph, M.; Hashmi, A. S. K. (Chem. Soc. Rev., 2012)

(untitled) - Abbiati, G.; Marinelli, F.; Rossi, E.; Arcadi, A. (Isr. J. Chem., 2013)

(untitled) - Chiarucci, M.; Bandini, M. (Beilstein J. Org. Chem., 2013)

(untitled) - López, F.; Mascareñas, J. L. (Beilstein J. Org. Chem., 2013)

(untitled) - Nunes dos Santos Comprido, L.; Hashmi, A. S. K. (Isr. J. Chem., 2013)

(untitled) - Ohno, H. (Isr. J. Chem., 2013)

(untitled) - Abbiati, G.; Rossi, E. (Beilstein J. Org. Chem., 2014)

(untitled) - Muratore, M. E.; Homs, A.; Obradors, C.; Echavarren, A. M. (Chem. – Asian J., 2014)

(untitled) - Xie, J.; Pan, C.; Abdukader, A.; Zhu, C. (Chem. Soc. Rev., 2014)

(untitled) - Yang, W.; Hashmi, A. S. K. (Chem. Soc. Rev., 2014)

(untitled) - Dorel, R.; Echavarren, A. M. (Chem. Rev., 2015)

(untitled) - Qian, D.; Zhang, J. (Chem. Soc. Rev., 2015)

(untitled) - Soriano, E.; Marco-Contelles, J. (Acc. Chem. Res., 2009)

(untitled) - Gaillard, S.; Cazin, C. S. J.; Nolan, S. P. (Acc. Chem. Res., 2012)

(untitled) - Alcaide, B.; Almendros, P. (Acc. Chem. Res., 2014)

(untitled) - Fensterbank, L.; Malacria, M. (Acc. Chem. Res., 2014)

(untitled) - Fürstner, A. (Acc. Chem. Res., 2014)

(untitled) - Hashmi, A. S. K. (Acc. Chem. Res., 2014)

(untitled) - Obradors, C.; Echavarren, A. M. (Acc. Chem. Res., 2014)

(untitled) - Wang, Y.-M.; Lackner, A. D.; Toste, F. D. (Acc. Chem. Res., 2014)

(untitled) - Yeom, H.-S.; Shin, S. (Acc. Chem. Res., 2014)

(untitled) - Zhang, D.-H.; Tang, X.-Y.; Shi, M. (Acc. Chem. Res., 2014)

(untitled) - Zhang, L. (Acc. Chem. Res., 2014)

(untitled) - Gorin, D. J.; Sherry, B. D.; Toste, F. D. (Chem. Rev., 2008)

(untitled) - Alcarazo, M.; Stork, T.; Anoop, A.; Thiel, W.; Fürstner, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Nolan, S. P. (Acc. Chem. Res., 2011)

(untitled) - Cera, G.; Bandini, M. (Isr. J. Chem., 2013)

(untitled) - Gatineau, D.; Goddard, J.-P.; Mouriès-Mansuy, V.; Fensterbank, L. (Isr. J. Chem., 2013)

(untitled) - Hopkinson, M. N.; Gee, A. D.; Gouverneur, V. (Chem. – Eur. J., 2011)

(untitled) - Wegner, H. A.; Auzias, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Brand, J. P.; Li, Y.; Waser, J. (Isr. J. Chem., 2013)

(untitled) - Zhang, G.; Peng, Y.; Cui, L.; Zhang, L. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ball, L. T.; Green, M.; Lloyd-Jones, G. C.; Russell, C. A. (Org. Lett., 2010)

(untitled) - Brenzovich, W. E., Jr; Benitez, D.; Lackner, A. D.; Shunatona, H. P.; Tkatchouk, E.; Goddard, W. A., III; Toste, F. D. (Angew. Chem., Int. Ed., 2010)

(untitled) - Brenzovich, W. E., Jr; Brazeau, J.-F.; Toste, F. D. (Org. Lett., 2010)

(untitled) - Hopkinson, M. N.; Tessier, A.; Salisbury, A.; Giuffredi, G. T.; Combettes, L. E.; Gee, A. D.; Gouverneur, V. (Chem. – Eur. J., 2010)

(untitled) - Melhado, A. D.; Brenzovich, W. E., Jr; Lackner, A. D.; Toste, F. D. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, G.; Cui, L.; Wang, Y.; Zhang, L. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, G.; Luo, Y.; Wang, Y.; Zhang, L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ball, L. T.; Lloyd-Jones, G. C.; Russell, C. A. (Chem. – Eur. J., 2012)

(untitled) - Zhang, R.; Xu, Q.; Chen, K.; Gu, P.; Shi, M. (Eur. J. Org. Chem., 2013)

(untitled) - Zhu, S.; Ye, L.; Wu, W.; Jiang, H. (Tetrahedron, 2013)

(untitled) - Jones, C. J.; Taube, D.; Ziatdinov, V. R.; Periana, R. A.; Nielsen, R. J.; Oxgaard, J.; Goddard, W. A., III (Angew. Chem., Int. Ed., 2004)

(untitled) - Wegner, H. A.; Ahles, S.; Neuburger, M. (Chem. – Eur. J., 2008)

(untitled) - Brand, J. P.; Charpentier, J.; Waser, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Cui, L.; Zhang, G.; Zhang, L. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Peng, Y.; Cui, L.; Zhang, G.; Zhang, L. (J. Am. Chem. Soc., 2009)

(untitled) - Brand, J. P.; Waser, J. (Angew. Chem., Int. Ed., 2010)

(untitled) - de Haro, T.; Nevado, C. (J. Am. Chem. Soc., 2010)

(untitled) - Hopkinson, M. N.; Ross, J. E.; Giuffredi, G. T.; Gee, A. D.; Gouverneur, V. (Org. Lett., 2010)

(untitled) - Qian, D.; Zhang, J. (Beilstein J. Org. Chem., 2011)

(untitled) - Brand, J. P.; Chevalley, C.; Scopelliti, R.; Waser, J. (Chem. – Eur. J., 2012)

(untitled) - Levin, M. D.; Toste, F. D. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ma, Y.; Zhang, S.; Yang, S.; Song, F.; You, J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Peng, H.; Xi, Y.; Ronaghi, N.; Dong, B.; Akhmedov, N. G.; Shi, X. (J. Am. Chem. Soc., 2014)

(untitled) - Ball, L. T.; Lloyd-Jones, G. C.; Russell, C. A. (Science, 2012)

(untitled) - Ball, L. T.; Lloyd-Jones, G. C.; Russell, C. A. (J. Am. Chem. Soc., 2014)

(untitled) - Kar, A.; Mangu, N.; Kaiser, H. M.; Beller, M.; Tse, M. K. (Chem. Commun., 2008)

(untitled) - Kar, A.; Mangu, N.; Kaiser, H. M.; Tse, M. K. (J. Organomet. Chem., 2009)

(untitled) - Wu, Q.; Du, C.; Huang, Y.; Liu, X.; Long, Z.; Song, F.; You, J. (Chem. Sci., 2015)

(untitled) - Mankad, N. P.; Toste, F. D. (J. Am. Chem. Soc., 2010)

(untitled) - Tkatchouk, E.; Mankad, N. P.; Benitez, D.; Goddard, W. A., III; Toste, F. D. (J. Am. Chem. Soc., 2011)

(untitled) - Hofer, M.; Nevado, C. (Eur. J. Inorg. Chem., 2012)

(untitled) - Cambeiro, X. C.; Boorman, T. C.; Lu, P.; Larrosa, I. (Angew. Chem., Int. Ed., 2013)

(untitled) - Hofer, M.; Nevado, C. (Tetrahedron, 2013)

(untitled) - Hofer, M.; Gomez-Bengoa, E.; Nevado, C. (Organometallics, 2014)

(untitled) - Winston, M. S.; Wolf, W. J.; Toste, F. D. (J. Am. Chem. Soc., 2014)

(untitled) - Wolf, W. J.; Winston, M. S.; Toste, F. D. (Nat. Chem., 2014)

(untitled) - Hata, K.; Segawa, Y.; Itami, K. (Chem. Commun., 2012)

(untitled) - Yoshidomi, T.; Segawa, Y.; Itami, K. (Chem. Commun., 2013)

(untitled) - Raubenheimer, H. G.; Toerien, J. G.; Kruger, G. J.; Otte, R.; van Zyl, W.; Olivier, P. (J. Organomet. Chem., 1994)

(untitled) - Strasser, C. E.; Stander-Grobler, E.; Schuster, O.; Cronje, S.; Raubenheimer, H. G. (Eur. J. Inorg. Chem., 2009)

(untitled) - Roselló-Merino, M.; Díez, J.; Conejero, S. (Chem. Commun., 2010)

(untitled) - Hollóczki, O.; Nyulászi, L. (J. Org. Chem., 2008)

(untitled) - Kassaee, M. Z.; Shakib, F. A.; Momeni, M. R.; Ghambarian, M.; Musavi, S. M. (Tetrahedron, 2009)

(untitled) - Tukov, A. A.; Normand, A. T.; Nechaev, M. S. (Dalton Trans., 2009)

(untitled) - Wang, L.; Kong, L.; Li, Y.; Ganguly, R.; Kinjo, R. (Chem. Commun., 2015)

(untitled) - Canac, Y.; Soleilhavoup, M.; Conejero, S.; Bertrand, G. (J. Organomet. Chem., 2004)

(untitled) - Melaimi, M.; Soleilhavoup, M.; Bertrand, G. (Angew. Chem., Int. Ed., 2010)

(untitled) - Martin, D.; Melaimi, M.; Soleilhavoup, M.; Bertrand, G. (Organometallics, 2011)

(untitled) - Zeng, X.; Frey, G. D.; Kinjo, R.; Donnadieu, B.; Bertrand, G. (J. Am. Chem. Soc., 2009)

(untitled) - Kinjo, R.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2011)

(untitled) - López-Gómez, M. J.; Martin, D.; Bertrand, G. (Chem. Commun., 2013)

(untitled) - Hu, X.; Martin, D.; Melaimi, M.; Bertrand, G. (J. Am. Chem. Soc., 2014)

(untitled) - Jin, L.; Weinberger, D. S.; Melaimi, M.; Moore, C. E.; Rheingold, A. L.; Bertrand, G. (Angew. Chem., Int. Ed., 2014)

From C–H to C–C Bonds: Cross-Dehydrogenative-Coupling - Ito, H.; Ueda, K.; Itami, K. (Cross-Dehydrogenative-Coupling Reactions without Metals, 2015)

(untitled) - Jean, A.; Cantat, J.; Bérard, D.; Bouchu, D.; Canesi, S. (Org. Lett., 2007)

(untitled) - Kita, Y.; Morimoto, K.; Ito, M.; Ogawa, C.; Goto, A.; Dohi, T. (J. Am. Chem. Soc., 2009)

(untitled) - Morimoto, K.; Yamaoka, N.; Ogawa, C.; Nakae, T.; Fujioka, H.; Dohi, T.; Kita, Y. (Org. Lett., 2010)

(untitled) - Chiong, H. A.; Daugulis, O. (Org. Lett., 2007)

(untitled) - Fall, Y.; Reynaud, C.; Doucet, H.; Santelli, M. (Eur. J. Org. Chem., 2009)

(untitled) - Roger, J.; Požgan, F.; Doucet, H. (Adv. Synth. Catal., 2010)

(untitled) - Gaillard, S.; Bantreil, X.; Slawin, A. M. Z.; Nolan, S. P. (Dalton Trans., 2009)
See for the synthesis and characterization of AuCl3(IPr) complex.